Valorization and recycling of packaging belts and post-consumer PET bottles in the manufacture of sand concrete (Fracture and Structural Integrity, 2022)
The valorization of local by-products in the manufacture of a new range of sand concrete and the improvement of their properties, will lead to seek an arrangement between performance and cost in order to achieve a resistant material. Waste recycling affects two very important affect namely the environmental impact and the economic impact. The main objective of our work is to contribute to optimize the formulation of sand concrete as part of the recovery of waste, which is harmful to the environment given its bulky and unattractive nature, it is waste plastic. Most PET bottles become waste after use, causing environmental problems. To solve this problem, a method for recycling PET bottles as fibers to strengthen concrete is proposed.Two types of plastic waste are added to sand concrete; the first concerns the recycling of post-consumer bottles in PET, in the form of polyester fiber supplied by the company RET-PLAST and the second type concerns the packaging belts made of polyethylene terephthalate (PET). The properties in the fresh state (workability and density) and in the hardened state (compressive strength, tensile strength and water absorption) of the various produced concretes are analyzed and compared against their respective controls. From the experimental results, it can be concluded that the reinforcement of the cement matrix with PET fibers with a rate of 1% improves the mechanical properties of sand concrete as well as a remarkable decrease in its water absorption capacity.
Keywords: Sand concrete; P.E.T fiber; Mechanical behavior; Water absorption; Environment